2021
DOI: 10.1021/acsenergylett.1c01811
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial Passivation Engineering of Perovskite Solar Cells with Fill Factor over 82% and Outstanding Operational Stability on n-i-p Architecture

Abstract: Tremendous efforts have been dedicated toward minimizing the open-circuit voltage deficits on perovskite solar cells (PSCs), and the fill factors are still relatively low. This hinders their further application in large scalable modules. Herein, we employ a newly designed ammonium salt, cyclohexylethylammonium iodide (CEAI), for interfacial engineering between the perovskite and hole-transporting layer (HTL), which enhanced the fill factor to 82.6% and consequent PCE of 23.57% on the target device. This can be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
116
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 136 publications
(118 citation statements)
references
References 38 publications
2
116
0
Order By: Relevance
“…From our measurements, we can assume that the 2D perovskite EBL can effectively suppress charge carrier recombination at the perovskite/back electrode interface of the device. [ 16,34,35 ]…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…From our measurements, we can assume that the 2D perovskite EBL can effectively suppress charge carrier recombination at the perovskite/back electrode interface of the device. [ 16,34,35 ]…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the energetic barrier induced by the higher conduction band of the 2D perovskite passivation layer compared to the 3D perovskite can effectively block electron back transfer. [ 15,16 ] Furthermore, the use of 2D perovskites having bulky ammonium cations can improve the stability of PSCs by protecting the underlying layers from external degradation factors such as moisture diffusion. [ 17,18 ]…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[31][32][33][34][35] A lack of in-depth understanding of the heterojunction interfaces and appropriate interface designs, specifically the buried interfaces under polycrystalline perovskite films, is impeding further advancements in perovskite photovoltaic performance and stability. [36][37][38][39][40][41][42] To date, many researches mainly focus on the top surfaces of perovskite. [43][44][45][46][47] However, due to the accumulation of deep-level trap states, it is known that unfavorable non-radiative recombination losses that impede device power outputs exist at the interfaces with bottom contact layers.…”
mentioning
confidence: 99%
“…[5][6][7][8][9] However, the formation of defects on the surface and grain boundaries of the perovskite films is inevitable when conventional solution-processed processes are used. [10,11] These defects provide sites for nonradiative recombination and play a role in the perovskite degradation which compromises both device performance and stability. [12,13] Theoretical studies have indicated that the defects mainly consisted of I vacancy defects (VI) and I vacancies replaced by Pb antisite defects (PbI) because of their low formation energy.…”
Section: Introductionmentioning
confidence: 99%